How Family's Support of Perseverance in Creative Efforts Influences the Originality of Children's Drawing During the Period of COVID-19 Pandemic? - Shi, Bowen; Xing, Ziwei; Yang, Mei; Tang, Chaoying (Frontiers in Psychology, 2021)
This study points out that families' support of perseverance in creative efforts will increase children's originality of creative drawing through students’ persistence in information searching. Data analysis based on 134 Chinese young students’ creative drawings and survey supports the above hypothesis. Moreover, students’ exposure to COVID-2019 pandemic positively moderates the relationship between supporting of perseverance and students’ search persistence, such that high exposure to COVID-19 pandemic will increase the positive relationship between support of perseverance and search persistence. And students’ prosocial motivation inhibits the influence of search persistence on originality. Contributions to the theory of children creativity are discussed.